2022
DOI: 10.3389/fmicb.2022.928967
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Mechanisms of Secondary Metabolites Promoted by the Interaction Between Endophytes and Plant Hosts

Abstract: Endophytes is a kind of microorganism resource with great potential medicinal value. The interactions between endophytes and host not only promote the growth and development of each other but also drive the biosynthesis of many new medicinal active substances. In this review, we summarized recent reports related to the interactions between endophytes and hosts, mainly regarding the research progress of endophytes affecting the growth and development of host plants, physiological stress and the synthesis of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 132 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…Additionally, the widespread use of these pesticides caused environmental pollution, and raised a lot of concerns regarding food safety and human health, 45,46 thus searching for new antimicrobials that are eco‐friendly and efficient is extremely important. Endophytic strains play significant roles in protecting host plants against the infection of pathogens by enhancing its immune system or directly inhibiting the growth of pathogens 17–19 . In the present study, the endophytes associated with the navel orange were investigated for their antimicrobial effects against the primary pathogens causing citrus canker and citrus blue mold diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the widespread use of these pesticides caused environmental pollution, and raised a lot of concerns regarding food safety and human health, 45,46 thus searching for new antimicrobials that are eco‐friendly and efficient is extremely important. Endophytic strains play significant roles in protecting host plants against the infection of pathogens by enhancing its immune system or directly inhibiting the growth of pathogens 17–19 . In the present study, the endophytes associated with the navel orange were investigated for their antimicrobial effects against the primary pathogens causing citrus canker and citrus blue mold diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The host offers endophytes a comfortable living environment and vital nutrients, in exchange, endophytes can help the host plant in fixing atmospheric and land nitrogen sources, and aid it to overcome some biotic or abiotic pressures 18 . In particular, some endophytes can produce bioactive secondary metabolites to protect the host plant by directly inhibiting the growth of pathogens, or by boosting the plant immunity through the induction of defense‐related genes 19 . Because of the unique living habitat and the complex relationships with host plant, endophytes are capable of producing biologically and structurally interesting metabolites, which are important resources for the discovery of highly potent agrochemicals with novel mechanisms of action 20,21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those bacteria also play an important role in the biocontrol process against plant pathogens by producing antimicrobial metabolites [ 34 ]. The interaction between the plant and its associated bacteria can also take a deeper connection where some endophytic bacteria can synthesize one or more of their host’s metabolites [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of active components of P. There are surplus number has been reported to control bacterial and fungal diseases by microorganisms or their metabolites/volatiles (Garbeva and Weisskopf, 2020;Li et al, 2022), whilst snippets of information were reported on plant viruses with microbial volatiles. Bacillus species produce a wide structural variability of secondary metabolites that exhibit strong antibacterial and antifungal activities (Stein, 2005;Sansinenea and Ortiz, 2011).…”
Section: Identification Of Metabolitesmentioning
confidence: 99%